Insights on the terminology and on some pathophysiological aspects of cluster headache and related conditions - Bordini, Carlos Alberto (Headache Medicine, 2023)
Introduction Cluster headache and the more recently reported “related conditions”, namely Chronic Paroxysmal Hemicrania, Short-lasting, unilateral, Neuralgiform Headache with Conjunctival Injection and Tearing (SUNCT) Syndrome and (possibly also) Hemicrania Continua, are one of the fascinating groups of conditions in Neurology whose cardinal features are the almost absolute unilaterality of pain, its excruciating severity, besides the prominent mainly facial autonomic disturbances and overall the intriguing biorhythmicity.Beyond any doubt, the progress of our knowledge about the mechanisms of these conditions has been considerable, but there is always room for reflection on where we are and where we can go. Objective The objectives of the present study are to analyze the metrics of publications on the pathophysiology of these conditions, to explore in detail how proper the term ”Trigeminal Autonomic Cephalgia” is, and to comment on their numerous synonyms. Comment Much is needed to know the exact structures and circuitry involved in the pathophysiology of these conditions; accordingly, a non-compromising and just descriptive term might be useful. Along this line of reasoning and bearing in mind the cardinal points of such conditions, namely, pain in the trigeminal territory, prominent autonomic symptoms, prominent chronobiological features, and the excruciating character of the pain, a terminological possibility would be: Unilateral with Prominent Rhythmicity and Autonomic Symptoms Excrutiating Cephalgia (UPRASEC).